2011
DOI: 10.1017/s0007114511006210
|View full text |Cite
|
Sign up to set email alerts
|

Egyptian sweet marjoram leaves protect against genotoxicity, immunosuppression and other complications induced by cyclophosphamide in albino rats

Abstract: Cyclophosphamide (CP) is one of the most popular alkylating anticancer drugs that show a high therapeutic index, despite the widespread side effects and toxicity particularly in high-dose regimens and long-term use. Here, we evaluated and compared the efficacy of two different doses (50 and 100 mg/kg body weight, given orally for 30 consecutive days) of Egyptian sweet marjoram leaf powder (MLP) and marjoram leaf aqueous extract (MLE) in alleviating the genotoxicity, immunosuppression and other complications in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 43 publications
0
16
0
3
Order By: Relevance
“…Several studies have reported that sweet marjoram leaves, especially in the form of an herbal tea, may be useful as immunostimulant and in reducing genotoxicity in patients under chemotherapeutic interventions, besides inhibiting the production of free radicals [3, 6]. Indeed, Khan et al [12] proposed that reducing the availability of the genotoxic metabolites of chemical carcinogens from the body, by forming more water soluble conjugates, will consequently decrease the chance of an interaction with DNA through adduct formation that may lead to cancer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported that sweet marjoram leaves, especially in the form of an herbal tea, may be useful as immunostimulant and in reducing genotoxicity in patients under chemotherapeutic interventions, besides inhibiting the production of free radicals [3, 6]. Indeed, Khan et al [12] proposed that reducing the availability of the genotoxic metabolites of chemical carcinogens from the body, by forming more water soluble conjugates, will consequently decrease the chance of an interaction with DNA through adduct formation that may lead to cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Origanum majorana L. or Majorana hortensis Moench is an aromatic plant rich in essential oils and commercially grown in southern Europe and in the Mediterranean region [2, 3]. It is popularly known as marjoram and has been used in the form of herbal infusions in folk medicine for asthma, cold, coughs, cramps, depression, dizziness, gastrointestinal disorders, hay fever, headache, toothache, and sinus congestion and as a diuretic and to promote menstruation [2, 3]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental tests were performed using the protocols of pre-treatment, simultaneous treatment, and post-treatment ( Figure 2) in relation to cyclophosphamide, which is an alkylating compound with an indirect action that is capable of establishing covalent bonds between base pairs of the DNA molecule and generating genotoxic damage and chromosomal instability (Ramadan et al, 2012). The experimental groups were subjected to peripheral blood collection through the puncture of the tail vein for the genotoxicity and antigenotoxicity (comet assay) and for mutagenicity and antimutagenicity (micronucleus assay) evaluation.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Extrusion of the drug by cell membrane pumps, increased DNA damage repair, redistribution of intracellular accumulation of drugs, modification of drug target molecules, suppression of druginduced apoptosis, up-regulation of lipids and other biochemical changes will also be the others reasons (Hong et al 2005). Ramadan et al (2012) reported that both sweet marjoram leaf powder and marjoram leaf aqueous extract significantly alleviated most side effects and toxicity of cyclophosphamide (one of the most popular alkylating anticancer drugs) treated rats (non-tumour bearing) including the increase in chromosomal aberrations of bone marrow cells and serum MDA level, the decrease in the level of serum Ig, the delayed type of hypersensitivity response as also the weights and cellularity of lymphoid organs, and myelosuppression, leucopenia, macrocytic normochromic anaemia as well as thrombocytopenia by reactivating the non-enzymic (reduced glutathione) and enzymic (catalase, glutathione peroxidase, glutathione S-transferase, superoxide dismutase) antioxidant system and increasing the mitotic index of bone marrow cells. In the study by Al-Howiriny et al (2009), ethanol extract of O. majorana L. significantly decreased the incidence of ulcers, basal gastric secretion and acid output in rats.…”
Section: Resultsmentioning
confidence: 99%